If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 20 = -3x + 50 Reorder the terms: 20 + 2x = -3x + 50 Reorder the terms: 20 + 2x = 50 + -3x Solving 20 + 2x = 50 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 20 + 2x + 3x = 50 + -3x + 3x Combine like terms: 2x + 3x = 5x 20 + 5x = 50 + -3x + 3x Combine like terms: -3x + 3x = 0 20 + 5x = 50 + 0 20 + 5x = 50 Add '-20' to each side of the equation. 20 + -20 + 5x = 50 + -20 Combine like terms: 20 + -20 = 0 0 + 5x = 50 + -20 5x = 50 + -20 Combine like terms: 50 + -20 = 30 5x = 30 Divide each side by '5'. x = 6 Simplifying x = 6
| 4(x-3)+7=-3 | | 7x+2(3x+7)=144 | | 6x^2+9x-4=38 | | ax^3+bx-5=0 | | D+8=-7 | | -4(n-b)=12 | | 9(n+6)-5(2+2n)=-8n+5n | | 5(x+4)+14=59 | | 21=3(c-9) | | 6x-2(-6+3)=120 | | 3a+3b+3c=3b | | 7x-2-3x=-10 | | x+3.6=0.5 | | 2(8+4*2)= | | Y=(2t^2)+1 | | 5x+7(4x+7)=-149 | | -6(2x-7)=-12x+42 | | 6-5x=-39 | | 27x^3+9x^2+3x-3=0 | | 0.83x=35 | | 30+8=74 | | 5(k-5)-4(k+1)-13=-33 | | x=x^2-4x+2 | | Y=2t+1 | | .5x-7=0.1(x+10) | | -6(2w+1)-w=33 | | .5x-7=.1(x+10) | | 7x-11=16-2x | | -6x-3x-15=-9-2x | | 8=-4(c+6) | | 2x+(2y-164)=992 | | 36-3(2w+1)=9w-3(w+2) |